Eight Supporting Factors for Students Success in Quran Memorization - Sabrina, Vinni; Oktavia, Gifa; Albizar, Albizar; Susanti, Hendra; AR, Fitra Murni; Suryani, Yuli (Khalifa Journal of Islamic Education, 2022)
Having the memorization of the quran is one of the identities that must be owned as the students at Sekolah Tinggi Agama Islam Pengembangan Ilmu Alquran (STAI-PIQ) Sumatera Barat, Indonesia. Memorizing the Quran is not an easy thing, in achieving success in memorizing the Quran, of course, there are various supporting factors. This study aimed to analyze the supporting factors of students’ success in memorizing the Quran. This study used a qualitative method with the type of case study. The data sources were taken from twelve informants through direct interviews using a set of interview protocols. The informants involved were selected by using a purposive sampling technique from three batches of entries, 2019, 2020, and 2021. All interview data were then analyzed thematically using Miles and Huberman approach. The research findings found eight factors that supported the success of memorizing the Quran, the eight factors were i) sincere intentions due to Allah S. W. T, ii) strong self-determination, iii) planning good memorization targets, iv) memorizing verses with correct recitation, v) always repeating the memorization diligently, vi) always being motivated by the supervisor, vii) living in the Quran environment, viii) using the right method. This study succeeded in revealing various factors that supported the success of students in memorizing the Quran. In fact, these eight findings can be used as a guide for students in achieving hafiz in the Quran.